Geology of the Mt. Riiser-Larsen area of the Napier Complex, Enderby Land, East Antarctica - Ishizuka, Hideo; Ishikawa, Masahiro; Hokada, Tomokazu; Suzuki, Satoko (National Institute of Polar Research, 1998)
P(論文) The summer party of the 38th Japanese Antarctic Research Expedition (1996-97) performed field work in the Mt. Riiser-Larsen area of the Archaean Napier Complex, Enderby Land, East Antarctica. The area is underlain by various kinds of metamorphic rocks and unmetamorphosed intrusive rocks. Of these, the metamorphic rocks are tentatively divided into the layered gneiss series, massive gneiss series, and transitional gneiss series. The layered gneiss series, occurring in the central to northwestern part of the area, is characterized by layering structure composed of several types of garnet felsic gneiss with subordinate amounts of orthopyroxene felsic gneiss, pelitic and mafic gneisses, impure quartzite, and metamorphosed banded iron formation. The massive gneiss series is predominant in the southern to southeastern part and consists mainly of massive orthopyroxene felsic gneiss, in which the layering structure is not conspicuous and the lithology is rather monotonous. The transitional gneiss series is developed between the layered and massive gneiss series, in which metamorphosed anorthosite and ultramafic rocks occur characteristically as thin layers or blocks or pods. Metamorphic foliation, which is almost always parallel to the layering structure, strikes NE-SW to E-W and dips at moderate to gentle angles (20-40°) to the south or southeast. The mineral associations indicate that the majority of the metamorphic rocks could belong to the high temperature granulite facies at metamorphic temperature higher than 1000℃. Unmetamorphosed doleritic intrusive rocks, so-called Amundsen Dikes, intrude throughout the area, striking N-S and NE-SW. Furthermore, there are many shear zones, following preexisting structures such as dike margins, in which the gneisses and dikes have been sheared to mylonites or pseudotachylite-like rocks. departmental bulletin paper